Edukasi Sodium Tripoliphosphat Sebagai Alternatif Pengganti Boraks Pada Pembuatan Kerupuk Desa Turusgede - Lestari, Lela; Annisa Yasmin; Aji Yudha; Dea Nurita (UNIB Press, 2023)
This service activity has the aim of providing socialization and education for kerupuk gendar (rice cracker) makers who still use borax. The object of this activity is the Kerupuk Gendar Manufacturing Center in Turusgede Village which has problems in the form of dependence on the use of borax to produce kerupuk gendar. The method used for this service activity is FGD, outreach and education, application and implementation of using alternative materials to replace borax, and evaluation through pre-test and post-test. The results of the socialization and education showed an increase in craftsmen's knowledge about the dangers of borax and alternative materials to replace borax by 80% and was able to increase in the desire to make borax-free crackers by 90%. The results of the FGD determined that the alternative material to replace borax which was considered suitable for making kerupuk gendar was Sodium Tripolyphosphate (STPP). Application and implementation activities in the form of experiments on making kerupuk gendar with the addition of STPP materials were considered successful. The craftsmen explained that there were several differences, namely in the form of the texture of the dough when it was still wet and when it was dry, the thickness of the crackers, the color of the crackers after they were fried, and the taste of the crackers. Kerupuk gendar with the addition of STPP has been standardized as evidenced by the results of laboratory tests which show that they are free of borax.